Implementation Of IoT In Nila Fish Cultivation With Bioflock System - Wasito, Endro; Prahara, Tahan; Nursyahid, Arif; ., Dadi; Anggraeni K., Sri (Politeknik Negeri Semarang, 2024)
In cultivating tilapia using the biofloc system, maintaining water quality (temperature, pH, turbidity) is not only for the health of the fish but also for the reproduction of the biofloc. So that water quality is known, sensors connected to IoT are installed. Sensor output data is processed by Arduino and sent to a data base server via the internet network so that water quality parameters can be monitored at any time via the internet network. This system was created in research entitled